Gambaran Ketangguhan Keluarga dalam Merawat Pasien Skizofrenia - Liyanovitasari; Puji Lestari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
The prevalence of Schizophrenia in adults is about 1 in 222 people (0.45%). Families caring for members suffering from schizophrenia need to build resilience to cope with the stress and pressure they face. Resilience is the process of staying firm and able to overcome existing sufferings, difficulties, and challenges. The purpose of this study is to find out the picture of family resilience in treating Schizophrenia patients. This type of research is quantitative observational with a descriptive approach. The population consists of all families caring for 100 schizophrenia patients. The number of samples in this study was 80 people with an accidental sampling technique. The family resilience measurement tool uses the Connor-Davidson Resillience Scale (CD-RISC) questionnaire containing 25 statements with aspects of emotional regulation, impulse control, optimism, analysis of the cause of problems, empathy, self-efficacy, and reaching out. Univariate analysis in this study includes frequency distribution. The results of the study showed that family resilience was in the high category as many as 49 people (61.3%), medium category as many as 30 people (37.5%) and low category as many as 1 person (1.2%). It is expected that families will increase family resilience by participating in self-efficacy training, learning skills in relieving existing emotions, focusing on optimism so that they can reduce the stress experienced in caring for their family members who suffer from schizophrenia.